2012
DOI: 10.1371/journal.pone.0030574
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Splice Sites Used for Generation of rev Transcripts in Human Immunodeficiency Virus Type 1 Subtype C Primary Isolates

Abstract: The HIV-1 primary transcript undergoes a complex splicing process by which more than 40 different spliced RNAs are generated. One of the factors contributing to HIV-1 splicing complexity is the multiplicity of 3′ splice sites (3'ss) used for generation of rev RNAs, with two 3'ss, A4a and A4b, being most commonly used, a third site, A4c, used less frequently, and two additional sites, A4d and A4e, reported in only two and one isolates, respectively. HIV-1 splicing has been analyzed mostly in subtype B isolates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
2
8
1
Order By: Relevance
“…The splicing differences seen between the 4-kb and 1.8-kb sizes in NL4-3 are also seen in pZM247Fv2. A previous study found high variation in A4 splice site usage among subtypes and samples (16,38). In this single sample, we did not see any new splice site usage, although the pZM247Fv2 sequence has a point mutation that completely inactivates A4d.…”
Section: Figcontrasting
confidence: 44%
“…The splicing differences seen between the 4-kb and 1.8-kb sizes in NL4-3 are also seen in pZM247Fv2. A previous study found high variation in A4 splice site usage among subtypes and samples (16,38). In this single sample, we did not see any new splice site usage, although the pZM247Fv2 sequence has a point mutation that completely inactivates A4d.…”
Section: Figcontrasting
confidence: 44%
“…The great majority of studies on HIV-1 RNA splicing have been performed with isolates of subtype B, which is predominant in Western countries. Published reports on non-subtype B viruses are limited to the study of two group O [ 11 , 34 ] and three subtype C [ 12 ] isolates. In these studies, RNA splice sites used by rev RNAs previously unreported in subtype B viruses were identified: A4e in a group O virus [ 11 ], A4f in two subtype C viruses, and A4g in one subtype C virus [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gag and Pol proteins are translated from the unspliced full-length viral mRNA, and the Env protein is translated from the spliced env -mRNA [1]. In contrast, it has been reported that human immunodeficiency virus (HIV) type 1, which is a complex retrovirus, could generate up to 40 different spliced RNAs using four 5’ss and nine 3’ss [2-4]. …”
Section: Introductionmentioning
confidence: 99%